UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH MENGGUNAKAN MEDIA PAPAN PANTUL SISWA KELAS VII SMPN 21 PONTIANAK - Gustian, Gustian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The problem in this study is how to improve the ability of passing under volleyball through the bouncing board media for students of class VII F SMPN 21 Pontianak. The purpose is to find out the improvement in the ability of basic techniques of volleyball lower passing through the bouncing board media. The research method is a qualitative descriptive method with the form of class action research (PTK). The research subjects were 35 students of class VII F SMPN 21 Pontianak. The data analysis technique uses the percentage of achievement of completeness. Conclusion The results of the research on the basic technique of passing down volleyball obtained a value for the pre-cycle of 17.14% complete value, 82.86% incomplete value. For cycle 1 the value is completed 42.86%, the value is not completed 57.15%. For cycle 2, the value is 100% complete, the value is 0.00% incomplete. The results of completeness in the pre-cycle were 17.14% (6 people), cycle 1 was 42.86% (15 people) and cycle 2 was 100% (35 people). Suggestions that can be used as a reference as a result of the conclusions of existing research are that students are expected to always be active and concentrated in participating in the learning process, especially the basic technical material of lower pasing so that the learning content delivered can be received properly.